Inovasi Daerah Sebagai Katalis Pertumbuhan Ekonomi: Studi Persepsi di Kabupaten Banyumas - Gunawan Adi Saputra Silalahi; Khoirunurrofik (Jurnal Bina Praja, 2024)
This study analyzed public perceptions of regional innovation in Banyuwangi Regency. This study was conducted at the Banyuwangi Regional Government, the most innovative region in the last 5 years. This study adopts the theory of Regional Innovation and indicators in the Global Innovation Index (GII) and the Regional Innovation Index (IID). Data collection was carried out online with 311 respondents (N-311). The analysis method used a descriptive method with the SPSS 2017 application. The results of the analysis show that there is a relationship between public perceptions of regional innovation, generally having a very good category, but the product sophistication variable has an index value of 4.17 with the smallest good category compared to the index values of other variables, this is in line with the achievement of the Banyuwangi Regency regional innovation index in 2023 with an index value of 84.19 which experienced a decrease previously the index value in 2022, namely 96.3 where product sophistication was the lowest with a value of 44.5%. At the end of the research section, the author tries to recommend that the Banyuwangi Regency government improve the credit and investment system to improve the market sophistication variable in the regional innovation index.